Pengaruh Love of Money, Machiavellian, dan Self Assesment System Terhadap Penggelapan Pajak - Bunga Natasya Salsabilaa; Eko Sasongko Priyadi (CV. ITTC INDONESIA, 2024)
The research aims to analyze the Love of Money, Machiavellian, and Self Assessment System Against Tax Evasion. This type of research is quantitative research. The population of this study is the Taxpayer Private Person Undergraduate Accounting of Pamulang University. Sampling using Slovin's formula. The number of samples distributed is 100 samples. The method of data collectio in this study is questionnaire. The data analysis techniques used are descriptive statistics, data quality tests, classical assumptions tests, hypothesis tests. Research results show that (1) Love of Money has no effect on tax evasion, (2) Machiavellian has no effect on tax evasion, (3) Self Assessment System has no effect on tax evasion.